Hikmat Dalam Misi Israel Menurut Ulangan 4: 5-8 - Paulus Dimas Prabowo (Sekolah Tinggi Teologi Arastamar Bengkulu, 2021)
The wisdom of Israel is linked to its mission. Another unique thing is that wisdom which is usually associated with divine power, intellect, spirituality, practical skills, and the meaning of life apparently is also associated with missions for all nations. Israel as God's chosen nation with a royal priesthood carries out a noble task to fulfill His promise to Abraham that his descendants will be a blessing to all tribes. In carrying out these responsibilities, Israel needed wisdom. Through exegesis studies of Deuteronomy 4: 5-8 and supported by literature studies, it can be found that the wisdom of Israel was implemented in obedience to the law of God. From this obedience, the nations will see the quality of their lives, hear their preaching about the LORD and His decrees, and recognize that Israel is a special nation until finally they are expected to give praise to God and even follow Him. This review also reveals the fact that the mission carried out by Israel is either centripetal or centrifugal. The results of this study can also be applied in the missionary task of believers today.